Clinical and molecular predictors of response and survival following venetoclax therapy in relapsed/refractory AML - Stahl, Maximilian (Blood Adv, 2021)
Azacitidine + venetoclax, decitabine + venetoclax, and low-dose cytarabine + venetoclax are now standard treatments for newly diagnosed older or unfit patients with acute myeloid leukemia (AML). Although these combinations are also commonly used in relapsed or refractory AML (RR-AML), clinical and molecular predictors of response and survival in RR-AML are incompletely understood. We retrospectively analyzed clinical and molecular characteristics and outcomes for 86 patients with RR-AML who were treated with venetoclax combinations. The complete remission (CR) or CR with incomplete hematologic recovery (CRi) rate was 24%, and the overall response rate was 31% with the inclusion of a morphologic leukemia-free state. Azacitidine + venetoclax resulted in higher response rates compared with low-dose cytarabine + venetoclax (49% vs 15%; P = .008). Median overall survival (OS) was 6.1 months, but it was significantly longer with azacitidine + venetoclax compared with low-dose cytarabine + venetoclax (25 vs 3.9 months; P = .003). This survival advantage of azacitidine + venetoclax over low-dose cytarabine + venetoclax persisted when patients were censored for subsequent allogeneic stem cell transplantation (8.1 vs 3.9 months; P = .035). Mutations in NPM1 were associated with higher response rates, whereas adverse cytogenetics and mutations in TP53, KRAS/NRAS, and SF3B1 were associated with worse OS. Relapse was driven by diverse mechanisms, including acquisition of novel mutations and an increase in cytogenetic complexity. Venetoclax combination therapy is effective in many patients with RR-AML, and pretreatment molecular characteristics may predict outcomes. Trials that evaluate novel agents in combination with venetoclax therapy in patients with RR-AML that have adverse risk genomic features are warranted.